Secure Sunday Briyani Ordering Management System with Two-Factor Authentication - clarissa kamaly,; HARUN, NUR ZIADAH HARUN (Applied Information Technology And Computer Science, 2023)
SECURE SUNDAY BRIYANI ORDERING MANAGEMENT SYSTEM WITH TWO-FACTOR AUTHENTICATION.